2005
DOI: 10.1091/mbc.e05-03-0216
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 Coordinates Vascular Smooth Muscle α-Actin Gene Activation by Transforming Growth Factor β1 and Thrombin during Differentiation of Human Pulmonary Myofibroblasts

Abstract: Profibrotic regulatory mechanisms for tissue repair after traumatic injury have developed under strong evolutionary pressure to rapidly stanch blood loss and close open wounds. We have examined the roles played by two profibrotic mediators, transforming growth factor ␤1 (TGF␤1) and thrombin, in directing expression of the vascular smooth muscle ␣-actin (SM␣A) gene, an important determinant of myofibroblast differentiation and early protein marker for stromal cell response to tissue injury. TGF␤1 is a well know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 60 publications
(88 reference statements)
4
67
1
Order By: Relevance
“…We previously showed by immunoblot and immunofluorescence microscopy that TGF␤1 substantially increased SM␣A mRNA and protein expression in early passage human pulmonary fibroblasts (Zhang et al, 2005). As shown in Figure 1a, TNF-␣ (10 ng/ml) provided to hPFBs 2 h before treatment with TGF␤1 (5 ng/ml) markedly reduced the accumulation of SM␣A protein relative to the level of expression noted in cells treated with TGF␤1 alone.…”
Section: Tnf-␣ Inhibits Tgf␤1-inducible Sm␣a Gene Activity In Human Pmentioning
confidence: 65%
See 3 more Smart Citations
“…We previously showed by immunoblot and immunofluorescence microscopy that TGF␤1 substantially increased SM␣A mRNA and protein expression in early passage human pulmonary fibroblasts (Zhang et al, 2005). As shown in Figure 1a, TNF-␣ (10 ng/ml) provided to hPFBs 2 h before treatment with TGF␤1 (5 ng/ml) markedly reduced the accumulation of SM␣A protein relative to the level of expression noted in cells treated with TGF␤1 alone.…”
Section: Tnf-␣ Inhibits Tgf␤1-inducible Sm␣a Gene Activity In Human Pmentioning
confidence: 65%
“…Synthetic oligonucleotide probes used in this report were derived from selected sequences present in the human SM␣A promoter Sun et al, 1995;Kelm et al, 1996;Subramanian et al, 2004;Zhang et al, 2005). Reaction mixtures containing protein extract (100 g of protein) and 3Ј-biotinylated oligonucleotides (100 pmol; Integrated DNA Technologies, Coralville, IA) were incubated in a buffer containing poly(dI-dC), 10 mM Tris, pH 7.5, 50 mM NaCl, 0.5 mM DTT, 0.5 mM EDTA, 0.12 mM PMSF, and 4% glycerol.…”
Section: Dna Binding Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several genes important for wound healing and cellular proliferation and survival are regulated by YB-1, including collagen alpha1 and alpha2 (Norman et al 2001;Higashi et al 2003), matrix metalloproteinase 2 (Mertens et al 1997), the B-chain isoform of plateletderived growth factor (Stenina et al 2000), vascular endothelial growth factor (Coles et al 2004), granulocyte-macrophage-colony stimulating factor (Coles et al 2000), and Fas death receptor (Lasham et al 2000); moreover, YB-1 can also regulate αSMA and human pulmonary myofibroblasts (Zhang et al 2005). Takahashi et al (2010) reported that YB-1 is increased in the angiogenic endothelial cells of various tumors and is involved in the growth of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%